2013
DOI: 10.1111/jeu.12031
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 of Bonamia ostreae: Characterization and Possible Correlation with Infection of the Flat Oyster, Ostrea edulis

Abstract: In this study, we described the cytosolic HSP90 of Bonamia ostreae, an intracellular parasite of Ostrea edulis hemocytes. The complete open reading frame was assembled by Rapid Amplification cDNA Ends reactions on cDNA of B. ostreae-infected hemocytes. HSP90 amplification was corroborated in infected oysters and B. ostreae purified cells. The functionality of the HSP90, studied by inhibitory assays with radicicol, suggests that this protein may play a role in hemocyte invasion. Our results inform the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Hemocytes internalyze parasites by endocytosis but B.ostreae seem to actively contribute to its own internalization [3]. It has recently been shown that a heat shock protein 90 (HSP90) is partly involved in parasite internalization [5]. Once internalized, B.ostreae induces some modifications of hemocyte activities including decrease of reactive oxygen species (ROS) production and esterase activities [4,6].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemocytes internalyze parasites by endocytosis but B.ostreae seem to actively contribute to its own internalization [3]. It has recently been shown that a heat shock protein 90 (HSP90) is partly involved in parasite internalization [5]. Once internalized, B.ostreae induces some modifications of hemocyte activities including decrease of reactive oxygen species (ROS) production and esterase activities [4,6].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ostreae was involved in its own internalization. Indeed, B. ostreae treatment consisting in blocking actin and HSP90 drastically reduced the percentage of "infected" cells [3,5,6].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A gene encoding B. ostreae heat shock protein 90 (HSP90) has recently been characterized, and the involvement of this protein in haemocyte invasion was investigated by pre-exposing parasites to radicicol, an HSP90-inhibitor. Haemocytes in contact with radicicol-exposed parasites appeared significantly less infected than haemocytes in contact with nontreated parasites (Prado-Alvarez et al 2013). Flow cytometry was used to demonstrate that live parasites are phagocytosed at higher rates than fluorescent beads .…”
Section: Host−parasite Interactionsmentioning
confidence: 99%
“…The inclusion of these functional genes in phylogenomics analyses clarified the phylogenetic position of this organism among rhizarian. Regarding B. ostreae, two actin genes and the HSP90 gene are the unique functional genes described to date and also placed Bonamia representatives among haplosporidians (López-Flores et al 2007, Prado-Alvarez et al 2013. Actin genes are highly conserved, broadly distributed and are widely used in phylogenetic studies of protozoans (Burki et al 2010;Leander and Keeling, 2004;López-Flores et al 2007).…”
Section: Introductionmentioning
confidence: 99%